Unveiling the anticancer effects of SGLT-2i: mechanisms and therapeutic potential - Sun, Min; Sun, Jilei; Sun, Wei; Li, Xiaonan; Wang, Zhe; Sun, Liwei; Wang, Yuehui (Frontiers in Pharmacology, 2024)
Cancer and diabetes are significant diseases that pose a threat to human health. Their interconnection is complex, particularly when they coexist, often necessitating multiple therapeutic approaches to attain remission. Sodium-glucose cotransporter protein 2 inhibitors (SGLT-2i) emerged as a treatment for hyperglycemia, but subsequently exhibited noteworthy extra-glycemic properties, such as being registered for the treatment of heart failure and chronic kidney disease, especially with co-existing albuminuria, prompting its assessment as a potential treatment for various non-metabolic diseases. Considering its overall tolerability and established use in diabetes management, SGLT-2i may be a promising candidate for cancer therapy and as a supplementary component to conventional treatments. This narrative review aimed to examine the potential roles and mechanisms of SGLT-2i in the management of diverse types of cancer. Future investigations should focus on elucidating the antitumor efficacy of individual SGLT-2i in different cancer types and exploring the underlying mechanisms. Additionally, clinical trials to evaluate the safety and feasibility of incorporating SGLT-2i into the treatment regimen of specific cancer patients and determining appropriate dosage combinations with established antitumor agents would be of significant interest.